Prevalence and Risk Factors of Anaplasma marginale Infections in Beef Cattle in Salakpra Wildlife Sanctuary, Kanchanaburi Province - Saetiew, Nantiya; Simking, Patcharathorn; Yatbantoong, Nantawan; Ninphet, Watchara; Laosomboon, Prapa; Pumrojana, Putthaphorn; Jittapalapong, Sathaporn (Journal of Mahanakorn Veterinary Medicine, 2018)
The objective of this study was to examine the prevalence and factors associated with Anaplasma marginale infections in beef cattle invading natural forest area of Salakpra Wildlife Sanctuary in Kanchanaburi province using polymerase chain reaction (PCR) assays. A total of 244 blood samples from beef cattle were examined for A. marginale. Factors associated with A. marginale infection including location, age, sex, herd size, insect abundant, deworming, domestic pet in household, tick existed in cattle and barn, and the grazing area management were statistically analyzed.The results revealed that 54.1% of cattle were positive for A. marginale infection. Bo Phloi District had the highest infection at 77.7% (73/125). Mueang and Sri Sawat District beef cattle were infected with the organism at the rate of 45.7% (43/94) and 28.1% (16/25), respectively. The potential significant factors associated with A. marginale infections were age, herd size and insect abundant (P<0.05). The present study has confirmed the presence of Anaplasmosis carriers, which have the potential role for transmission to nearby livestock or wildlife.